Red as Blood, White as Snow: Chromatic Symbolism of Womanhood in Fairy Tales - Vaz da Silva, Francisco (14th Congress of the International Society for Folk-Narrative Research, 2005)
Since Berlin and Kay’s classic study on Basic Color Terms: Their Universality and Evolution, several authors have examined the universal chromatic triangle of white, red and black in several perspectives, regarding different cultures. The involvement of eminent anthropologists (such as Rodney Needham, Marshall Sahlins, and Victor Turner, to name but a few) in discussing the semantics of the chromatic triangle indicates the importance of this topic for the study of traditional symbolism. But so far, attention has been mostly focused on ritual, and sights have been set on non-European cultures. Differently, this paper addresses the problem from the perspective of European fairytales. Twelfth-century Chrétien de Troyes has famously let us know that the sight of three drops of blood on snow reminds Perceval of his sweetheart. Seven centuries afterwards, the Grimms still knew that a queen looking at three drops of her own blood on the snow was bound to think, "Would that I had a child as white as snow, as red as blood, and as black as the wood of the window-frame." Nowadays, we do not really know much about the underlying symbolism. Still, the image is so vivid in the fairytale world that the time seems ripe for a theoretical contribution from folkloristics.